1984
DOI: 10.1017/s0007485300015741
|View full text |Cite
|
Sign up to set email alerts
|

Implications for comparability of laboratory experiments revealed in studies on the effects of population density on vigour in Coptotermes lacteus (Froggatt) and Nasutitermes exitiosus (Hill) (Isoptera: Rhinotermitidae & Termitidae)

Abstract: The vigour, i.e. survival and wood consumption, of groups of Coptotermes lacteus (Frogg.) and Nasutitermes exitiosus (Hill) was measured when termites were kept at different population densities by changing group size and/or volume of the holding container. A characteristic pattern emerged for subterranean termite species. At low population densities (<0-01 g termites/ml), performance improved with an increase in group size; at higher densities, it tended to decline. The impact of altering group size and conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…We do find a strong effect of social group size on survivorship (Table 1), but this effect was not related to resistance. Termites living in larger groups live significantly longer, confirming that for many species of termites group size is positively correlated with survivorship (Lenz and Barrett 1984;Rosengaus et al 1998b). We do not rule out the possibility of a density effect on resistance, and future studies could increase power to detect it over previous studies with larger sample sizes and increased ranges in size classes, perhaps spanning three or more orders of magnitude.…”
Section: Effect Of Group Size On Disease Resistancementioning
confidence: 66%
“…We do find a strong effect of social group size on survivorship (Table 1), but this effect was not related to resistance. Termites living in larger groups live significantly longer, confirming that for many species of termites group size is positively correlated with survivorship (Lenz and Barrett 1984;Rosengaus et al 1998b). We do not rule out the possibility of a density effect on resistance, and future studies could increase power to detect it over previous studies with larger sample sizes and increased ranges in size classes, perhaps spanning three or more orders of magnitude.…”
Section: Effect Of Group Size On Disease Resistancementioning
confidence: 66%
“…In this study, C. formosanus treated with control solution and kept alone died more than twice as fast as those kept in small groups, and C. formosanus kept in large groups (1000–2000) with colony material, such as in the bottles received at EBCL, could live 6 months or longer. That group size is positively correlated with survivorship is well known ( Lenz and Barrett , 1984; Rosengaus et al, 1998b), particularly when termites are exposed to fungal pathogens ( Boucias et al, 1996; Rosengaus et al, 1998b). In our experiments, the relationship between fungal dose and median survivorship was weaker among grouped termites than among termites kept alone, but among grouped termites Pfu02031 reduced median survivorship significantly more than did M. anisopliae .…”
Section: Discussionmentioning
confidence: 98%
“…Jones (1990) found that while large groups of termites tunneled more than small groups in soils treated with chlordane, chlorpyrifos, or permethrin, group size had different effects on mortality in different soil treatments. Several experiments have demonstrated correlations between termite survival rates and population density (Lenz et al, 1984;Lenz, 2009;Santos et al, 2004). At population densities below 0.1 g termites / ml, Lenz et al (1984) found that, in the absence of termiticide treatment, survival of Coptotermes lacteus (Froggatt) and Nasutitermes exitiosus (Hill) increased with population density.…”
Section: Termite Pressure and Susceptibilitymentioning
confidence: 99%
“…Several experiments have demonstrated correlations between termite survival rates and population density (Lenz et al, 1984;Lenz, 2009;Santos et al, 2004). At population densities below 0.1 g termites / ml, Lenz et al (1984) found that, in the absence of termiticide treatment, survival of Coptotermes lacteus (Froggatt) and Nasutitermes exitiosus (Hill) increased with population density. Susceptibility differences occur among termite species and colonies.…”
Section: Termite Pressure and Susceptibilitymentioning
confidence: 99%